2022
DOI: 10.3390/ma15165770
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 2-Methacryloyloxyethyl Phosphorylcholine Polymer Materials on Orthodontic Friction and Attachment of Oral Bacteria

Abstract: There is no clinical evidence of the usage of 2-methacryloyloxyethyl phosphorylcholine (MPC) polymers in dental practice. We performed in vitro studies to determine whether the application of an MPC coating to stainless steel orthodontic wires confers low-friction and antimicrobial properties to these wires. The friction test on MPC-coated wires was performed using a precision universal/tensile tester. MPC polymer was coated on a 50 × 50 mm stainless steel plate, and samples were assessed using an antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Quantitative assays revealed a substantially lower level of S. marcescens adhesion to the PMPC-modified surface of lehfilcon A compared to traditional soft contact lenses ( Figure 1 ), and this pattern was maintained across media conditions ( Figure 2 ) and across strains ( Figure 6 ). These results agree with prior reports of the anti-biofouling properties of other MPC-modified medical devices and test surfaces, including stainless steel [ 38 , 39 ], dental resins [ 40 , 41 , 42 ], absorbable sutures [ 43 ], and for a variety of organisms, including S. aureus [ 38 , 43 ], S. epidermidis [ 38 ], P. aeruginosa [ 38 ], S. mutans [ 39 , 41 ], P. gingivalis [ 39 ], and Candida spp. [ 40 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Quantitative assays revealed a substantially lower level of S. marcescens adhesion to the PMPC-modified surface of lehfilcon A compared to traditional soft contact lenses ( Figure 1 ), and this pattern was maintained across media conditions ( Figure 2 ) and across strains ( Figure 6 ). These results agree with prior reports of the anti-biofouling properties of other MPC-modified medical devices and test surfaces, including stainless steel [ 38 , 39 ], dental resins [ 40 , 41 , 42 ], absorbable sutures [ 43 ], and for a variety of organisms, including S. aureus [ 38 , 43 ], S. epidermidis [ 38 ], P. aeruginosa [ 38 ], S. mutans [ 39 , 41 ], P. gingivalis [ 39 ], and Candida spp. [ 40 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…The materials tested are comfilcon A, senofilcon A, omafilcon B, fanfilcon A, balafilcon A, senofilcon C, and lehfilcon A. Lehfilcon A is a newly marketed silicon hydrogel contact lens with a surface modification containing poly-(2-methacryloyloxyethyl phosphorylcholine) (PMPC) [ 35 , 36 ]. MPC has been described to impart anti-biofouling properties to numerous base substrates [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…They covered SS archwires with an MPC coating and performed tensile tests using a bracket-archwire combination to demonstrate the coating’s ability to reduce friction. Furthermore, they directly measured the efficiency of tooth movement using an in vitro experimental tooth movement model at 50 g and 100 g traction force, and finally confirmed that the SS archwire coating with MPC improves the efficiency of tooth movement by reducing the occurrence of friction [ 96 ]. This experimental design has provided ideas for subsequent studies.…”
Section: Friction Reduction Coatingsmentioning
confidence: 99%
“…MPC polymer coatings inhibit the adhesion of Streptococcus mutans to SS archwires [ 96 ]. CTS has been used as an antibacterial material in the resin for bonding orthodontic attachments, with the purpose of controlling enamel demineralization, but it has not been tested for its antibacterial properties as a surface coating for orthodontic attachments, which is a direction that could be developed in the future [ 24 ].…”
Section: Antibacterial Coatingsmentioning
confidence: 99%
“…Lehfilcon A is a recently developed SiHy contact lens material that is surface modified with poly-(2-methacryloyloxyethyl phosphorylcholine) (PMPC) [ 46 , 47 ]. MPC is remarkable for its anti-biofouling properties and has been shown to be effective on a multitude of substrates [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Previously, lehfilcon A was demonstrated to reduce protein and lipid deposition compared to its silicon hydrogel base material [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%